1982
DOI: 10.1073/pnas.79.3.815
|View full text |Cite
|
Sign up to set email alerts
|

Increase in apparent compressibility of cytochrome c upon oxidation.

Abstract: BiophysicsIncrease in apparent compressibility of cytochrome c upon oxidation (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 38 publications
6
55
1
Order By: Relevance
“…[184][185][186] Ultrasonic velocimetry was used to measure the root mean square volume fluctuations and apparent molal and adiabatic compressibilities of ferro-and ferricytochrome c. 185 The compressibilities and volume fluctuations were greater for the oxidized form indicating increased flexibility. Recently, however, Sagle et al 187 elegantly demonstrated using site directed isotope labeling and FTIR that oxidation of Cyt C residues near the heme moiety increases local protein unfolding without increasing flexibility.…”
Section: Oxidationmentioning
confidence: 99%
“…[184][185][186] Ultrasonic velocimetry was used to measure the root mean square volume fluctuations and apparent molal and adiabatic compressibilities of ferro-and ferricytochrome c. 185 The compressibilities and volume fluctuations were greater for the oxidized form indicating increased flexibility. Recently, however, Sagle et al 187 elegantly demonstrated using site directed isotope labeling and FTIR that oxidation of Cyt C residues near the heme moiety increases local protein unfolding without increasing flexibility.…”
Section: Oxidationmentioning
confidence: 99%
“…4 graphic evidence shows that there are small differences between the tertiary structures of MetMb and deoxy Mb (15,16); moreover, in the former, H20 is the sixth ligand, whereas, in the latter, the iron has only five ligands. Recent measurements of compressibility in cytochrome c point to a substantial difference in dynamic properties between the ferri and ferro forms of the protein, despite the identical time-averaged structure of these proteins (25). Therefore, it is, perhaps not surprising to find differences in dynamics between MetMb and deoxy Mb.…”
mentioning
confidence: 91%
“…For cytochrome c the differences in the effective radii of the oxidized and reduced states are thought to result from a combination of electrostatic and conformational changes. Small structural differences have been identified between the two redox forms of cytochrome c (25,26). In addition it has been suggested that phosphate binding to lysine-rich sites at low ionic strengths in the oxidized state may contribute to the increase in the effec- 1 The abbreviation used is: ANS, 8-anilino-1-napthalenesulphonate.…”
Section: Thementioning
confidence: 99%